1998
DOI: 10.1093/ije/27.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lung function and blood pressure in Chinese men and women of Beijing and Guangzhou

Abstract: These results suggest a statistically significant, though weak, inverse relationship between lung function and blood pressure in Chinese men and women. This association is largely attributable to age and is present prospectively only in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 31 publications
4
43
2
1
Order By: Relevance
“…It has been hypothesised that the association can be explained by the confounding effect of age, since lung function decreases and BP increases with age [17]. However, our results remained significant after adjustment for age.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…It has been hypothesised that the association can be explained by the confounding effect of age, since lung function decreases and BP increases with age [17]. However, our results remained significant after adjustment for age.…”
Section: Discussioncontrasting
confidence: 73%
“…This is especially notable in patients with chronic obstructive pulmonary disease (COPD) where it has been shown that even moderate reductions in expiratory flow volumes elevate the risk for CVD two-to three-fold [10][11][12][13]. An inverse relationship between lung function and blood pressure has been reported in several studies [14][15][16][17]. Although the mechanism underlying this relationship remains unclear, it has been shown that individuals with reduced lung function have higher levels of C-reactive protein, fibrinogen and other systemic inflammatory markers when compared to those with normal lung function [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…These findings were consistent with previous studies that found that inter-individual variation in lung function level in early adulthood to be associated with future development of hypertension. 9,11,12 Our study extended this previous understanding of association between inter-individual differences in lung function and hypertension to include intra-individual change of lung function from peak and hypertension in a generally healthy sample. Lung function deterioration can be seen as an independent factor associated with future hypertension incidence, even for those with low normal lung function.…”
Section: Discussionmentioning
confidence: 66%
“…Reports have shown inverse cross-sectional associations between lung function measures (especially FVC and FEV1 but not FEV1/FVC) and blood pressure; 5,9,10 however, analyses have been inconsistent. 9,11 On the contrary, cohort studies have shown that lower lung function measures at baseline were consistently associated with higher incidence of subsequent hypertension, 9,11,12 suggesting more rapid blood pressure elevation in persons who initially have lower lung function. This study aimed to assess whether steeper decline in lung function, even within the normal range, is associated with higher incidence of hypertension statistically controlling for level of baseline lung function.…”
mentioning
confidence: 99%
“…Reduced lung function, as measured by forced expiratory volume in 1 s (FEV 1 ) and forced vital capacity (FVC), is associated with an increased risk for the development of hypertension [1][2][3] and cardiovascular disease (CVD) [4]. Although the association between lung function and CVD is clear, the mechanistic underpinnings of this association remain largely unexplained.…”
Section: Introductionmentioning
confidence: 99%